ANALISIS LAPORAN KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PERUSAHAAN PADA PT. UNILEVER INDONESIA TBK: (PERUSAHAAN YANG TERDAFTAR DI BEI PERIODE 2018-2020) - Sofyan Hadi (Jurnal Ilmiah Akuntansi dan Manajemen, 2022)
This study aims to determine how the company's financial performance at PT. Unilever Indonesia, Tbk., in terms of liquidity ratio, solvency ratio, profitability ratio, and activity ratio. The research method used in this research is quantitative research with a descriptive approach. Then a time series analysis is performed. The results of the research from the liquidity ratio is described from the current ratio and the ratio still show the company is in a bad condition. Meanwhile, the solvency ratio is described from the debt-to-asset ratio and the debt-to-equity ratio shows the company is in an unhealthy condition. However, from the profitability ratios is described from the gross profit margin ratio, net profit margin, operating profit margin, ROA, and ROE, it shows that the company is in a good and healthy condition in obtaining profits, only ROE has decreased. And the last of the activity ratio is described from the asset turnover ratio, working capital turnover ratio, fixed asset turnover ratio, and inventory turnover ratio, the company is in in poor condition as the percentage in this ratio has decreased every year.